Sistem Indera pada Manusia Ketertarikan Antara Gangguan pada Sistem Indera dan Kesehatan Manusia - Ariska Sukma Romadhani; Aryna Agustin Nur Hidayah; Ardina Rayshabilah; Astrid Tyas Wardhani; Ayu Wulandari; Liss Dyah Dewi Arini (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Disorders of the human sensory system can significantly impact quality of life, affecting communication skills, mobility, and daily activities. This study analyzes the relationship between sensory system disorders and human health using a descriptive qualitative approach. The method involves collecting data from relevant literature and thematic analysis to understand the causes, impacts, and preventive measures for sensory disorders. The research findings indicate that early detection and appropriate handling are crucial to mitigate negative effects. Public awareness of the importance of maintaining sensory system health also needs to be enhanced through education and collaboration among various stakeholders.